The Impact Of Implementing Team Accelerated Instruction On Motivation And Learning Achievement Of Class V Primary Schools In Lumajang District - Sapi'i Imam (Journal of Education Technology and Inovation, 2024)
This study aims to improve Learning Motivation and Learning Outcomes Together, especially in Islamic Religious Education subjects for students as a whole. The role of Islamic Religious Education teachers in using the Cooperative Learning Type Team Accelerated Instruction model shows the importance of real context according to the situation in the environment by the students themselves in thinking about identifying problems in learning so that the concepts received by students are more meaningful. In this study, the data collection techniques used were observation, questionnaire and documentation. The research is in the form of a quantitative experiment with the research subjects are fifth grade students of SDN Gelang 08 Sumberbaru-Jember, odd semester, 2023-2024 academic year totaling 30 students.... The data in this study are quantitative data with analysis of validity, reliability and instrument tests in the form of homogeneity, and autocorrelation. The results of the percentage of success of this study show: (1) the effect of the Cooperative Learning Type Team Accelerated Instruction model on increasing Learning Motivation together is 23 (75.6%) students (2) the effect of the Cooperative Learning Type Team Accelerated Instruction model on increasing Learning Results together is 23 students (76.5%), and (3) the effect of the Cooperative Learning Type Team Accelerated Instruction model on increasing Learning Motivation a is 24 students (86.1%). This means that the application of the Cooperative Learning Type Team Accelerated Instruction model in improving Learning Motivation and Learning Outcomes Together for students has a significant effect.